Obacunone Photoprotective Effects against Solar-Simulated Radiation-Induced Molecular Modifications in Primary Keratinocytes and Full-Thickness Human Skin - Montero, Paula; Villarroel, Maria José; Roger, Inés; Morell, Anselm; Milara, Javier; Cortijo, Julio (International journal of molecular sciences, 2023)
Solar radiation can cause damage to the skin, leading to various adverse effects such as sunburn, reactive oxygen species production, inflammation, DNA damage, and photoaging. To study the potential of photoprotective agents, full-thickness skin models are increasingly being used as in vitro tools. One promising approach to photoprotection involves targeting the redox-sensitive transcription factor Nrf2, which is responsible for regulating various cellular defense mechanisms, including the antioxidant response, inflammatory signaling, and DNA repair. Obacunone, a natural triterpenoid, has been identified as a potent Nrf2 agonist. The present study aims to evaluate the relevance of full-thickness (FT) skin models in photoprotection studies and to explore the potential photoprotective effects of obacunone on those models and in human keratinocytes. Phenion® full-thickness skin models and keratinocytes were incubated with increasing concentrations of obacunone and irradiated with solar-simulated radiation (SSR). Various photodamage markers were evaluated, including histological integrity, oxidative stress, apoptosis, inflammation, photoaging-related dermal markers, and photocarcinogenesis markers. Increasing doses of SSR were found to modulate various biomarkers related to sun damage in the FT skin models. However, obacunone attenuated cytotoxicity, inflammation, oxidative stress, sunburn reaction, photoaging, and photocarcinogenesis in both keratinocytes and full thickness skin models exposed to SSR. These results suggest that obacunone may have potential as a photoprotective agent for preventing the harmful effects of solar radiation on the skin.
Keywords: Radiation-Protective Agents; ultrafialové záření; Inflammation; Ultraviolet Rays; Skin; radioprotektivní látky; sluneční spáleniny; zánět; Keratinocytes; lidé; NF-E2-Related Factor 2; Sunburn; Humans; faktor 2 související s NF-E2; keratinocyty; kůže